Contact-Dependent Granzyme B-Mediated Cytotoxicity of Th17-Polarized Cells Toward Human Oligodendrocytes - Jamann, Hélène; Cui, Qiao-Ling; Desu, Haritha L.; Pernin, Florian; Tastet, Olivier; Halaweh, Alexandre; Farzam-kia, Negar; Mamane, Victoria Hannah; Ouédraogo, Oumarou; Cleret-Buhot, Aurélie; Daigneault, Audrey; Balthazard, Renaud; et al. (Frontiers in Immunology, 2022)
Multiple sclerosis (MS) is characterized by the loss of myelin and of myelin-producing oligodendrocytes (OLs) in the central nervous system (CNS). Pro-inflammatory CD4+ Th17 cells are considered pathogenic in MS and are harmful to OLs. We investigated the mechanisms driving human CD4+ T cell-mediated OL cell death. Using fluorescent and brightfield in vitro live imaging, we found that compared to Th2-polarized cells, Th17-polarized cells show greater interactions with primary human OLs and human oligodendrocytic cell line MO3.13, displaying longer duration of contact, lower mean speed and higher rate of vesicle-like structure formation at the sites of contact. Using single cell RNA sequencing, we assessed the transcriptomic profile of primary human OLs and Th17-polarized cells in direct contact or separated by an insert. We showed that upon close interaction, OLs upregulate the expression of mRNA coding for chemokines and antioxidant/anti-apoptotic molecules, while Th17-polarized cells upregulate the expression of mRNA coding for chemokines and pro-inflammatory cytokines such as IL-17A, IFN-γ and granzyme B. We found that secretion of CCL3, CXCL10, IFN-γ, TNFα and granzyme B is induced upon direct contact in co-cultures of human Th17-polarized cells with human OLs. In addition, we validated by flow cytometry and immunofluorescence that granzyme B levels are upregulated in Th17-polarized compared to Th2-polarized cells, and are even higher in Th17-polarized cells upon direct contact with OLs or MO3.13 cells compared to Th17-polarized cells separated from OLs by an insert. Moreover, granzyme B is detected in OLs and MO3.13 cells following direct contact with Th17-polarized cells, suggesting the release of granzyme B from Th17-polarized cells into OLs/MO3.13 cells. To confirm granzyme B–mediated cytotoxicity towards OLs, we showed that recombinant human granzyme B can induce OLs and MO3.13 cells death. Furthermore, pre-treatment of Th17-polarized cells with an irreversible granzyme B blocker (Ac-IEPD-CHO) or a natural granzyme B blocker (serpina3N) improved survival of MO3.13 cells upon co-culture with Th17 cells. In conclusion, we showed that human Th17-polarized cells form biologically significant contacts with human OLs and exert direct toxicity by releasing granzyme B.